2006
DOI: 10.1097/01.wnr.0000220136.98918.41
|View full text |Cite
|
Sign up to set email alerts
|

Dextromethorphan protects male but not female mice with brain ischemia

Abstract: The non-competitive N-methyl-D-aspartate receptor antagonist dextromethorphan is protective against some types of brain injury. Unilateral carotid ligation in postnatal day 12 CD1 mice produces ischemic brain injury. To evaluate the neuroprotective potential of dextromethorphan against ischemic injury in the immature brain, seven litters of postnatal day 12 CD1 mice received either dextromethorphan or vehicle after a unilateral carotid ligation. Only the male pups were protected, and brain injury was unchanged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
1
14
1
Order By: Relevance
“…These papers support the hypothesis that gender-specific cell death pathways are conserved across species in the perinatal brain. We have also shown that the glutamate antagonist dextromethorphan is protective against stroke in male but not female mice at 12 days of age 144. This finding also supports the greater influence of the excitotoxic pathway in immature males.…”
Section: Apoptotic Mechanisms Involved In Hypoxia-ischemiasupporting
confidence: 78%
“…These papers support the hypothesis that gender-specific cell death pathways are conserved across species in the perinatal brain. We have also shown that the glutamate antagonist dextromethorphan is protective against stroke in male but not female mice at 12 days of age 144. This finding also supports the greater influence of the excitotoxic pathway in immature males.…”
Section: Apoptotic Mechanisms Involved In Hypoxia-ischemiasupporting
confidence: 78%
“…For males, androgens improve developing neuron survival in the hypothalamus (36,37) and visual cortex (38). Male neonatal mice injured by unilateral carotid artery ligation also respond preferentially to the neuroprotective effects of dextromethorphan (39). In contrast, hypoxia triggers IGF-1 expression only in developing females, and estrogen reduces brain injury in adult animal models of stroke (40,41).…”
mentioning
confidence: 99%
“…On the morning of P12, equal numbers of male and female animals (Table 1) were subjected to modified Levine procedure (unilateral carotid ligation only) for producing ischemic brain injury as previously described under isoflurane anesthesia [6,7]. Previous studies have demonstrated that early cortical reperfusion occurs in the carotid ligation model [8], thereby mimicking the clinical situation in patients.…”
Section: Surgical Procedures For Ischemic Modelmentioning
confidence: 99%